Analysis of High Order Thinking Skills of High School Students in Solving Heat and Thermodynamics Problems - Wakhidyah, Sasti Handayani; Mudakir, Imam; Wahyuni, Sri (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Higher order thinking skills are skills that 21st century students should have in order to compete globally. Higher-order thinking skills involve complex thinking processes, including analysing, evaluating and creating. This study aims to analyse students' higher order thinking skills in solving heat and thermodynamics problems. The samples used in this study were grade 12 students in the 2024/2025 academic year, as many as 64 students. Data collection was carried out through the results of high thinking ability tests on heat and thermodynamics material with Bloom's tachnosomy domain levels C4, C5, and C6. The method used is quantitative method with purposive sampling technique. The results of this study, students have the ability to analyse (C4) by 61.34%, the ability to evaluate (C5) by 26%, and the ability to create (C6) by 12.66%. The conclusion of this study is that students are in the good category in the analysing aspect, the less category in the evaluating aspect and the very less category in the creating aspect. This means that students can complete the completion stage but are less able to compile information so that they are unable to produce perfect answers.